Laura Siburian in Digital Lens: Analyzing Identity and Its Influence on Social Media: Laura Siburian dalam Lensa Digital: Menganalisis Identitas dan Pengaruhnya di Media Sosial - Octavia, Amanda; Rosalinda, Syakirah (Procedia of Social Sciences and Humanities, 2025)
This research uses a descriptive qualitative approach with content analysis method to analyze how Laura Siburian builds her digital identity on social media. An in-depth analysis of posts, comments, and user interactions made it possible to identify the communication strategies used, themes raised, and audience responses. This research aims to understand how the construction of an influencer's digital identity can influence public perception and shape opinions.